EFFECTS OF INTERNAL AUDIT PRACTICE ON ORGANIZATIONAL PERFORMANCE OF REMITTANCE COMPANIES IN MODADISHUSOMALIA - AHMED DAHIR, ABDULAHI; OMAR, NAGIB (IJRDO - Journal of Business Management, 2016)
The purpose of the study was to conduct a survey of internal audit practice factors affecting in the performance of remittance companies in Mogadishu-Somalia. The study design was used is descriptive survey, the target population of the study was remittance companies locate in Bakara market, and they are 15 remittance companies, the employees worked that 15 remittance companies are 402 employees. A sample size of 200 respondents was selected using Slog van’s formula. Data collection methods used included questionnaire. The selection sample technique was purposive or judgmental approach. Data was analyzed using SPSS version 22. The key findings were that internal audit practice drivers individually had a positive influence on the organizational performance of remittance companies in Mogadishu-Somalia. The overall results indicated that there was a significant linear relationship between internal audit independence, internal audit quality, internal control system and audit risk assessments have positive significant relationship with Remittance Company’s performance in Somalia. The conclusions were established that internal audit practice drivers were found to significantly and positively influence organizational performance of remittance companies in Mogadishu, Somalia. It is recommended that managers should study and select the driver that best suits their companies in order to achieve maximum performance.